Clinical Handbook of Fear and Anxiety: Maintenance Processes and Treatment Mechanisms. 2020
DOI: 10.1037/0000150-019
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological enhancement of extinction learning.

Abstract: Cognitive behavior therapy (CBT) is the gold-standard treatment for anxiety disorders, obsessive-compulsive disorder (OCD), and posttraumatic stress disorder (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…There is great interest in finding ways to alter extinction learning processes to oppose these traumatic memories ( Kida, 2019 ). Pre-clinical studies have suggested timed brain stimulation ( Milad and Quirk, 2002 ; Vidal-Gonzalez et al, 2006 ; Bukalo et al, 2015 ; Likhtik and Paz, 2015 ), glutamatergic agonists ( Norberg et al, 2008 ; La Buissonnière-Ariza et al, 2020 ), and timed increases in adrenal hormones ( de Kloet et al, 2005 , 2006 ; McEwen, 2005 ; Klaassens et al, 2012 ; Iob et al, 2020 ) as potential strategies for augmenting extinction. Invasive brain stimulation presents a challenge to routine clinical practice, and pharmacologic strategies have shown limited effectiveness in formal trials ( Storch et al, 2007 ; Litz et al, 2012 ; Ressler, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in finding ways to alter extinction learning processes to oppose these traumatic memories ( Kida, 2019 ). Pre-clinical studies have suggested timed brain stimulation ( Milad and Quirk, 2002 ; Vidal-Gonzalez et al, 2006 ; Bukalo et al, 2015 ; Likhtik and Paz, 2015 ), glutamatergic agonists ( Norberg et al, 2008 ; La Buissonnière-Ariza et al, 2020 ), and timed increases in adrenal hormones ( de Kloet et al, 2005 , 2006 ; McEwen, 2005 ; Klaassens et al, 2012 ; Iob et al, 2020 ) as potential strategies for augmenting extinction. Invasive brain stimulation presents a challenge to routine clinical practice, and pharmacologic strategies have shown limited effectiveness in formal trials ( Storch et al, 2007 ; Litz et al, 2012 ; Ressler, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in finding ways to alter or augment extinction learning processes that could oppose these traumatic memories (13). Pre-clinical studies have suggested timed brain stimulation (1417), glutamatergic agonists (18,19), and timed increases in adrenal hormones (15) as potential strategies for augmenting extinction. Invasive brain stimulation presents a challenge to routine clinical practice, and pharmacologic strategies have shown limited effectiveness in formal trials (2022).…”
Section: Introductionmentioning
confidence: 99%